Pemanfaatan Aplikasi Tiktok sebagai Media Dakwah Oleh Ustadzah Oki Setiana Dewi - Efendi, Erwan; Nabila Putri Amanda; Maimunah, Siti (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
With current developments, everyone can access information via the internet. One of them is by using social media in everyday life, namely the TikTok application. Ustadzah Oki SetianaDewi uses TikTok to preach by producing content that follows current viral trends. His preaching style is characterized by his soft speech, simple but easy to understand and understand, and interesting. The video content presented by Ustadzah Oki Setiana Dewi can attract the attention of the public, especially youth so that it can improve moral quality in accordance with Islamic teachings. This research aims to find out Ustadzah Oki Setiana Dewi in using the TikTok application as a medium for preaching to encourage people to do good things in accordance with the commands of Allah SWT. As a result of this research, researchers used descriptive analysis, and the results of this research also used regression test variables, coefficient tests, multiple linear, correlation and determination. Because the results of this research show a high level on Ustadzah Oki Setiana Dewi's TikTok account, which currently has 1.9 million followers, 28.2 million likes and 1403 videos. Therefore, Ustadzah Oki Setiana Dewi's TikTok account provides many benefits and good examples for her followers. In this way, many people apply the good things conveyed by Ustadzah Oki Setiana Dewi.